(3GdTGed aj GdCOhjI GdeaQOIs - (3GHf GdUhQjs
(3ChdgG (B:s
(3GdMeO dgd GdaGWQ GdHOjY GdYdGe bGd GdGeGe GdC(B'(3Xe GdGaVd eGdc eedcI GdaGVFd hGdMce LGeY GdaQhY hGdCUhd CHh SYOI Hf GdGeGe GHj eSde GdTjQGRj s
(3BNQgG (B:s
(3efgG GSJYeGd GdeQge GdGShO hSGFQ GdeNaVGJ GdbhjI eKd GdGHGQ GdeMQb R hGdeQh GWQGa Gd SeGb JeJ GdebGdI GdChdj s
(3hJhLO efg fSNI CNQj aj GdeYgO (B126 (3WH Yf LGeYI jhJGs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3SGeO (B(2108) s
Keywords: (3eJaQbGJs